Matriarchinie Izraela w tradycji żydowskiej - Chrostowski, Waldemar (Biblica et Patristica Thoruniensia, 2011)
The four “mothers” (Sarah, Rebekah, Lea and Rachela), the wives of the three patriarchs (Abraham, Isaac and Jacob), played significant roles in the second part of Genesis narratives. In Jewish tradition these biblical stories were broadly developed and enriched, stressing the virtues of the four matriarchs as examples to follow by Jewish girls and women. The article shows the different streams and contents of the very vivid and instructive traditions going back to antiquity.